Training for mid-level managers (MLM). Module 5, Monitoring the immunization system (World Health Organization, 2008)
These modules provide immunization managers with up-to-date information. The introducition of new vaccines is put into its day-to-day context. Module 5 encourages mid-level managers to measure the performance of the immunization system by passive data collection (monthly reports), and active data collection (supervisory visits).
Keywords: výzkumná zpráva; Health Personnel; vakcíny; primární prevence; zdravotnický personál; výchova a vzdělávání pracovníků ve zdravotnictví; Primary Prevention; Visitors to Patients; preventivní medicína; sběr dat; Vaccines; Education; imunizace; Immunization; Research Report; poskytování zdravotní péče; Delivery of Health Care; Immunization Programs; Nursing Assessment; výchova a vzdělávání; Data Collection; očkovací programy; ošetřovatelské zhodnocení; návštěvníci pacientů; epidemiologie